(untitled) (International Journal of Scientific Trends, 2026)
This article examines the institutional frameworks and mechanisms for implementing modern social approaches in Turkic states within the context of globalization and socio-political transformation. The study analyzes the role of education systems, governance structures, and social institutions in shaping contemporary social policies. A comparative approach is applied to identify common patterns and national specificities in countries such as Uzbekistan, Türkiye, Kazakhstan, and Azerbaijan. The findings reveal that the integration of innovative technologies, competency-based education, and regional cooperation plays a crucial role in enhancing the effectiveness of social approaches.